CURRENT STATUS OF THE CASPIAN REGION - T. Sakulyeva (Вестник университета)
The Caspian region plays an extremely important role in ensuring regional and interregional transport links in the areas of the West - East and North -Yug. For all the littoral states of the region is important in terms of not only resource wealth, but also, above all, creating a zone of sustainable socio-economic development.